Pengembangan PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK PEMBELAJARAN FISIKA SMP/MTs BERORIENTASI KETERAMPILAN 4C PADA MATA PELAJARAN IPA: PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK PEMBELAJARAN FISIKA SMP/MTs BERORIENTASI KETERAMPILAN 4C PADA MATA PELAJARAN IPA - dini khoirunisak dini khoirunisak; Abdul Majid; Firdaus Firdaus (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2023)
The aim of this research is to produce LKPD for SMP/MTs physics learning which can improve the ability of students with a series of 4C skill activities which are included in the LKPD. This type of research is R&D using the Tiagharajan model, namely 4-D which includes delfinel (development), design (design), delvellolp (development), disselminatel (distribution). The design of the research subject was 36 class VII students of MTs Ma'arif NU Kelrttelk. Data analysis techniques used descriptive qualitative and quantitative analysis. The data analyzed using qualitative descriptive included the eligibility of student worksheets from material experts, media experts, and student relations, while quantitative descriptive included the results of increasing learning outcomes with pre-test and poll-test questions. From the calculation of the material expert validation questionnaire, the result was 91.05%, so that the LKPD included in the Golri category was very feasible. From the calculation of the media expert validation questionnaire, the result was 87.99%, so that the LKPD included in the score category was very feasible. From the calculation of the science educator practitioner's questionnaire, the result was 86.35%, based on the practicality criteria of science educators, LKPD included in the very practical category. From the calculation of the students' research question papers, an average of 79.96% was obtained, so based on the practicality criterion, the LKPD was practical. The research results showed that there was an increase in student learning outcomes after learning was done using the 4C skill learning LKPD. This can be seen from the results of the analysis of the N-Gain test results of learning selbelsar 0.42 katelgolri "seldang".